Coefficient estimates for a subclass of close-to-convex functions associated with tilted koebe functions / Ain Fatihah Ishak, Nurul Hasya Nasuha Muazam and Nurul Natasya Hasni - Ishak, Ain Fatihah; Muazam, Nurul Hasya Nasuha; Hasni, Nurul Natasya (2019)
Every class of function has different extremal properties such as coefficient estimates, arc length, distortion theorem, radius properties, growth theorem, center and radius and area. Furthern1ore, it becomes a huge problem to define a suitable method in finding the extremal properties for this new class of function and the coefficient estimates. In this research, we define a subclass of close-to-convex functions associated with generalized Koebe functions and find extremal properties for this generalized Koebe functions.